FROM STANDARD TO TERRITORY: THE ROLE OF NURSES IN IMPLEMENTING THE "NOW THERE ARE SPECIALISTS" PROGRAM IN THE BRAZILIAN AMAZON – AN EXPERIENCE REPORT IN HUMAITÁ/AM, LÁBREA/AM AND THE DISTRICT OF SANTO ANTÔNIO DO MATUPI (MANICORÉ, AM) - dos Santos, José Maria Viana (Seven Editora, 2026)
Introduction: Timely access to specialized care remains one of the main challenges of the Brazilian Unified Health System (SUS), particularly in Amazonian territories marked by long distances, care gaps, and weaknesses in the regional organization of health networks (Giovanella et al., 2020; Garnelo et al., 2017). In response to this scenario, the Ministry of Health instituted, through Provisional Measure No. 1,301 of May 30, 2025, subsequently regulated by Ordinance GM/MS No. 7,266 of June 18, 2025, and in the context of the Public Health Emergency declared by Ordinance GM/MS No. 7,061 of June 6, 2025, the Agora Tem Especialistas Program, with operational support from the Brazilian Agency for Support to SUS Management (AgSUS). The program is structured around regulated access, comprehensive care, and the use of mobile specialized care units (Brasil, 2025a; Brasil, 2025b; Brasil, 2025c). Objective: To report and analyze the role of nurses in the implementation of the Agora Tem Especialistas Program in Amazonian territories, emphasizing processes of intergovernmental articulation, organization of access regulation through SISREG and e-SUS Regulação, community mobilization, and the operation of mobile units structured according to the logic of the Comprehensive Care Offer (Organização da Oferta do Cuidado Integral – OCI).Methods: A descriptive qualitative study in the form of an experience report, based on participant observation and reflective systematization of activities carried out between 2025 and 2026 in the municipalities of Humaitá and Lábrea and in the district of Santo Antônio do Matupi, in the municipality of Manicoré, Amazonas. Field notes, regulatory documents, meeting minutes, institutional instruments, and evidence of formal recognition by local managers were used.Results: The experience highlighted the central role of nurses as technical-political articulators in translating national guidelines into territorial practices, with emphasis on: organization of access exclusively through regulation systems (SISREG and e-SUS Regulação); adoption of the OCI logic (consultation, examination, and follow-up); implementation of mobile units characterized as customized trailers equipped with waiting areas, medical offices, ultrasound and mammography rooms, elevators for accessibility, climate-controlled and computerized environments; articulation with health surveillance and patient safety; and the innovative strategy of community mobilization through Community Health Workers. The case of Santo Antônio do Matupi stands out as the first district in the state of Amazonas to receive the Program, as well as the replicability of the experience, evidenced by a formal request for technical support from the municipality of Lábrea.Conclusion: Nurses emerged as strategic actors in the implementation of the Agora Tem Especialistas Program in Amazonian territories, mediating the articulation between public policy, health management, and the community, and contributing to the consolidation of a model of regulated and humanized specialized care oriented toward the quality of the clinical encounter, in line with the principles of equity and comprehensiveness of the SUS.DOI: https://doi.org/10.56238/sevened2026.008-113